Prophylactic Antibiotic Analysis in Obs-Gyn, Orthopedics, Gastrointestinal Surgery at a South Tangerang Hospital, January-March 2024 - Nurjaman, Evelina Endang; Andriani, Helen (UI Scholars Hub, 2026)
Inappropriate use of prophylactic antibiotics (PAs) remains a primary driver of antimicrobial resistance (AMR); however, global adherence to established prescribing guidelines remains suboptimal. This study aimed to analyze the compliance and rationality of PA prescription and to evaluate the underlying causes of physician non-adherence in obstetrics, orthopedic, and gastrointestinal surgeries at a hospital in South Tangerang City, Indonesia. Adopting a mixed-methods approach, this investigation combined a quantitative assessment of 208 surgical patient records (January–March 2024) with qualitative exploratory interviews conducted with three specialist peer group heads. This design allowed the triangulation of prescribing data with underlying clinical perspectives. PA rationality was assessed based on four criteria: indication, agent type, timing, and duration. Univariate analysis was used to examine the relationship between physician characteristics and compliance. The qualitative findings were analyzed using the Capability, Opportunity, Motivation – Behavior (COM-B) behavioral model. Overall compliance with all four PA criteria was poor, at only 9% (18 of 208 surgeries). Low adherence was particularly noted in agent selection (33%) and administration timing (42%). Orthopedic surgery showed the lowest compliance in terms of indication and duration. Univariate analysis indicated that only surgical procedure type significantly influenced compliance (p = 0.039). Qualitative analysis revealed that non-adherence was primarily driven by the fear of surgical site infection (SSI) and the belief that broad-spectrum agents are more effective. Notably, despite poor compliance, no incidence of SSI (0%) was reported during the 30–90-day post-procedure follow-up. Consistently poor compliance highlights significant gaps in procedural implementation and physician motivation regarding reasonable PA use. Targeted interventions focusing on standardized procedures, evidence-based education, and systemic monitoring are essential to improve prescription practices and mitigate the risk of AMR development.